The coding of valence and identity in the mammalian taste system - Wang, Li (Nature, 2018)
The ability of the taste system to identify a tastant (what does it taste like?) enables animals to recognize and discriminate between the different basic taste qualities(1,2). The valence of a tastant (is it appetitive or aversive?) specifies its hedonic value, and the execution of selective behaviors. Here we examine how sweet and bitter are afforded valence versus identity. We show that sweet and bitter cortex project to topographically distinct areas of the amygdala, with strong segregation of neural projections conveying appetitive versus aversive taste signals. By manipulating selective taste inputs to the amygdala, we show that it is possible to impose positive or negative valence to a neutral water stimulus, and even to reverse the hedonic value of a sweet or bitter tastant. Remarkably, animals with silenced amygdala no longer exhibit behavior that reflects the valence associated with direct stimulation of taste cortex, or with delivery of sweet and bitter chemicals. Nonetheless, these animals can still identify and discriminate between tastants, just as wildtype controls do. These results help explain how the taste system generates stereotypic and predetermined attractive and aversive taste behaviors, and substantiate distinct neural substrates for the discrimination of taste identity and the assignment of valence.